Civil society and postwar Pacific Basin reconciliation wounds, scars and healing /cedited by Yasuko Claremont - Claremont, Yasuko 1944- (Routledge studies in the modern history of Asia, 2018)
This book brings together discussions of leading aspects and repercussions of the Asia-Pacific War, which still have huge relevance today. From the development of war guilt to the vivid effect of art on bringing alive the realities of the war, it analyses a diversity of post-war issues in the Pacific Basin. Organised into five parts, the book begins by scrutinizing the conflicting attitudes towards Japanese post-war society and identifies the various legacies of the war. It also provides an examination of the aftermath of Hiroshima and Nagaski, before studying contemporary civil society and analysing the way memories of the war have changed with time. Each of the chapters discusses the Japanese government's inability to achieve reconciliation with its neighbours, despite the passage of over 70 years, and the denial of the atrocities committed by the Imperial Army. Arguing that this policy of continuous denial has triggered the rise of civil movements in Japan, this book will be useful to students and scholars of Japanese History and Japanese Studies in general